2011
DOI: 10.3233/jpd-2011-0003
|View full text |Cite
|
Sign up to set email alerts
|

Restorative Effects of Platelet Derived Growth Factor-BB in Rodent Models of Parkinson's Disease

Abstract: Parkinson's disease is characterized by motor deficits caused by loss of midbrain dopaminergic neurons. Neurotrophic factors and cell transplantation have partially restored function in models of Parkinson's disease, but have had limited effects in humans. Here we show that intracerebroventricular administration of platelet-derived growth factor-BB can offer an alternative strategy to restore function in Parkinson's disease; In animal models of nigrostriatal injury, a two weeks treatment with plateletderived g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
49
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(54 citation statements)
references
References 46 publications
2
49
0
3
Order By: Relevance
“…Increasing the generation or promoting the survival of new neurons is an interesting option in stroke. Moreover, studies in rodents have suggested that promoting cell proliferation in the subventricular zone can have a positive effect in models of Parkinson's disease, likely mediated by the new cells having a neurotrophic effect on the nigro-striatal system (Androutsellis-Theotokis et al, 2009;Zachrisson et al, 2011). Investigating how striatal neurogenesis is potentially affected in pathological situations and identifying factors that promote the renewal of striatal neurons may facilitate the development of therapeutic strategies to improve functional recovery after injury or to tackle neurodegenerative disorders.…”
Section: Discussionmentioning
confidence: 99%
“…Increasing the generation or promoting the survival of new neurons is an interesting option in stroke. Moreover, studies in rodents have suggested that promoting cell proliferation in the subventricular zone can have a positive effect in models of Parkinson's disease, likely mediated by the new cells having a neurotrophic effect on the nigro-striatal system (Androutsellis-Theotokis et al, 2009;Zachrisson et al, 2011). Investigating how striatal neurogenesis is potentially affected in pathological situations and identifying factors that promote the renewal of striatal neurons may facilitate the development of therapeutic strategies to improve functional recovery after injury or to tackle neurodegenerative disorders.…”
Section: Discussionmentioning
confidence: 99%
“…PDGF-BB was also increased in brain after treatment with 6-OHDA suggesting a compensatory response [98]. Along this line, PDGF-BB injections induced functional recovery and provided neuroprotection of the lesioned nigrastriatal system [99]. Data showed that PDGF-BB might act not directly on dopaminergic neurons, but on neural progenitor and stem cells in the subventricular zone to enhance neurogenesis [99].…”
Section: Pdgfmentioning
confidence: 96%
“…Along this line, PDGF-BB injections induced functional recovery and provided neuroprotection of the lesioned nigrastriatal system [99]. Data showed that PDGF-BB might act not directly on dopaminergic neurons, but on neural progenitor and stem cells in the subventricular zone to enhance neurogenesis [99]. Together these results raised the possibility that stimulation of neurogenesis in the brain can enhance recovery and possibly halt the process of cell degeneration in PD.…”
Section: Pdgfmentioning
confidence: 98%
“…However, digestion of the CS-GAGs is believed to liberate ligands such as various growth factors that aid plasticity [23][24][25]. Given that several growth factors are known to enhance survival of dopaminergic neurones, such as glial-derived neurotrophic factor, cerebral dopaminergic neurotrophic factor, platelet-derived growth factor-BB and fibroblast growth factor 20 [26][27][28][29][30], the liberation of these growth factors following digestion could certainly explain the protective effects seen here. Further studies will be required to establish the underlying mechanisms.…”
Section: Discussionmentioning
confidence: 85%